Progressive MS: from pathophysiology to drug discovery. (October 2015) - Salvetti, Marco; Landsman, Douglas; Schwarz-Lam, Peter; Comi, Giancarlo; Thompson, Alan J; Fox, Robert J
Progressive multiple sclerosis (MS) will be a major area of research interest for years to come. No treatments exist and success in the field will generalise to other neurological conditions where neurodegeneration coexists with neuroinflammation. The issue is complex, and interdisciplinary approaches – uniting scientists with different competences (neurobiology, immunogenetics, etc.) and 'mindsets' (academia and industry) – will be decisive. The International Progressive MS Alliance is catalysing this process through various initiatives, the most recent of which was a meeting where scientists from academia (also outside the MS field) and from industry reviewed data and strategies to determine the next steps towards the translation of current knowledge into effective therapies. Key findings are: (i). Concerted efforts are essential to prioritise pathogenetic mechanisms according to impact on the disease and druggability. (ii). Combination therapies will probably be needed, possibly early in the disease, along with new trial designs and treatment schedules. (iii). Drug screenings are a pragmatic approach hopefully enriched by the use of neural and oligodendrocyte progenitors differentiated from induced pluripotent stem cells (iPSCs). (iv). The field of network biology will increase our ability to predict therapeutic targets. (v). Genome-wide association studies (GWAS) must try to identify variants associated with disease progression.